2010
DOI: 10.1007/s10103-010-0846-1
|View full text |Cite
|
Sign up to set email alerts
|

Six-month follow-up multicenter prospective study of 368 patients, phototypes III to V, on epilation efficacy using an 810-nm diode laser at low fluence

Abstract: Laser hair removal is currently a popular cosmetic procedure. Traditional high-fluence laser treatment for hair elimination is associated with discomfort and adverse events and it is restricted to low phototype skins. A multicenter study of hair epilation with low fluences and high repetition pulse rate using an 810-nm diode laser was carried out on 368 patients (phototypes III to V) to test its efficacy in a 6-month follow-up after five treatments on the face and various body areas. Objective and subjective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
5
16
2
2
Order By: Relevance
“…On average, we consider that the clearances achieved were good in the context of the literature , and very good in comparison with our previous experience with other equipment . The efficacy percentages obtained appear lower than those achieved by Paasch et al in a single patient with more suitable hair removal characteristics, using lower (and less painful) fluences, with the same laser .…”
Section: Discussionsupporting
confidence: 75%
“…On average, we consider that the clearances achieved were good in the context of the literature , and very good in comparison with our previous experience with other equipment . The efficacy percentages obtained appear lower than those achieved by Paasch et al in a single patient with more suitable hair removal characteristics, using lower (and less painful) fluences, with the same laser .…”
Section: Discussionsupporting
confidence: 75%
“…Studies using the diode laser have recently suggested a shift away from the criterion standard high‐fluence devices in favor of a low‐fluence (5–15 J/cm 2 ) approach. The latter provides comparable hair reduction, less discomfort, and fewer adverse effects even when treating phototype V skin and tanned individuals . The most common side effects were slight and transient erythema and pigmentary changes.…”
Section: Diodementioning
confidence: 98%
“…Lastly, it is interesting to compare the current results for this home‐use device to published results for prescription‐use devices. To this end, Table 4 summarizes some of the published results for diode lasers, in which it can be seen that a wide range of results are reported with long‐term hair removal (6 months or more) ranging from at least 34% to 65% under a variety of conditions 2, 3, 9, 18–24. In light of this, the present study demonstrates that the home‐use laser of the current study can produce results that are generally comparable to professional prescription‐use diode lasers when used in a series of treatments on indicated users and according to its instructions for use.…”
Section: Discussionmentioning
confidence: 54%